Enhancing the Ontario Internationally Educated Nurses Course Consortium Competency-Bridging Program of Study: Evaluation of a Competency-Based Approach to Meet Registered Nurse Practice Registration Requirements - Woodend, Kirsten; Bhatti, Ayesha; Bradley, Patricia; Manafo, Elizabeth; Patrick, Linda; Santa Mina, Elaine (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
The effective integration of internationally educated nurses (IENs) into healthcare organizations is essential for the sustainability of our healthcare system. The IEN program was initiated in 2017, with an enhanced program of study commencing in 2018. To assess the relevance, design, and effectiveness of this enhanced IEN program. The evaluation involved a review of existing program documents and interviews with 34 key informants, covering three evaluation domains: relevance, design, and effectiveness. The revised IEN program of study remains pertinent. There remains a need for programs and initiatives that assist IENs in bridging their competency gaps to practice as registered nurses (RNs). From a design perspective, the program of study met the needs of IENs and successfully reached its target audience. The program proved effective; it achieved the expected outcomes and was delivered efficiently. Students and graduates reported that the courses were well-structured, comprehensive, and taught by competent instructors. Stakeholders and program participants agreed that the program offers culturally appropriate, ethical practice and exposes students to diverse nursing contexts. The enhanced program of study effectively addresses the needs of IENs by providing an accessible, flexible, and high-quality pathway for RN licensure.